A Pilot Randomized, Controlled Trial of Metformin versus Insulin in Women with Type 2 Diabetes Mellitus during Pregnancy - Refuerzo, Jerrie S.; Gowen, Rose; Pedroza, Claudia; Hutchinson, Maria; Blackwell, Sean C.; Ramin, Susan (American Journal of Perinatology, 2015)
Objective Few studies support oral diabetic treatment in pregnant women with type 2 diabetes mellitus (T2DM). The objective of this study was to compare the effects of metformin versus insulin on achieving glycemic control and improving maternal and neonatal outcomes in pregnant women with T2DM.Study Design A pilot randomized, controlled trial was conducted of metformin versus insulin for the treatment of T2DM during pregnancy. The primary outcome was glycemic control measured with hemoglobin A1c < 7% at delivery. Maternal and neonatal outcomes were compared between groups.Results In this study, 8 women received metformin and 11 received insulin. All women in both groups achieved glycemic control by delivery (HgbA1c: metformin 5.96 ± 5.88 vs. insulin 6.34 ± 0.92%). There were similar rates of cesarean delivery, birth weights, neonatal intensive care unit admissions, respiratory distress syndrome, and neonatal dextrose treatment between groups. There was one case of fetal macrosomia in the insulin group, one case of shoulder dystocia in the metformin group and no cases of failed metformin therapy.Conclusion In this pilot study, glycemic control was achieved in women who received metformin and insulin. Larger studies are needed to determine whether metformin can be considered a reasonable alternative to insulin in pregnant women with T2DM.
Keywords: type 2 diabetes mellitus; pregnancy; metformin